PHYSICOCHEMICAL CHARACTERIZATION OF ÑUÑA BEAN (Phaseolus vulgaris L.) PROTEIN EXTRACT - Vargas-Salazar, Tania Alejandra; Wilkinson, Kevin A; Urquiaga-Zavaleta, Josué Manuel; Rodríguez-Zevallos, Antonio Ricardo (Vitae, 2020)
Background: Although legume protein extracts are useful in food preparation and processing as foam stabilizers and as viscosity, palatability and nutrition enhancers, many legume proteins from South America have not been characterized extensively. One such legume is the ñuña bean (Phaseolus vulgaris L.), which is cooked using dry heat until the cotyledons rapidly expand with a pop. The bean is widely cultivated in the Andes, but almost unknown elsewhere. Objective & Methods: In this study, we characterized ten functional properties of a ñuña protein extract using standard food analysis methods. Results: The extract was similar to other legume protein extracts for many properties (amino acid profile, proximate analysis, yield, water absorption, color, isoelectric point, and thermogravimetric analysis). The electrophoretic analysis revealed that the sample was nearly pure phaseolin. Additionally, the ability to form foam and increase solution viscosity were comparatively low when contrasted to other extracts. Conclusion: These properties make ñuña protein extract useful as a nearly pure phaseolin nutrition enhancer in beverages where foaming and high viscosity are undesirable, such as in fortified beverages, drinkable yogurts, or protein supplements. The extract may also have relevance as a weight-loss supplement. Therefore, we expect that incorporating ñuña protein in processed foods would be a straightforward process.